2017
DOI: 10.1152/ajpregu.00202.2017
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching by metal centered porphyrins and poryphyrin enzymes

Abstract: Fluorescence spectroscopy and microscopy have been used extensively to monitor biomolecules, especially reactive oxygen species (ROS) and, more recently, reactive sulfide (RSS) species. Nearly all fluorophores are either excited by or emit light between 450 and 550 nm, which is similar to the absorbance of heme proteins and metal-centered porphyrins. Here we examined the effects of catalase (Cat), reduced and oxidized hemoglobin (Hb and metHb), albumin (alb), manganese (III) tetrakis (4-benzoic acid) porphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Heme quenching of pocket tryptophan and tyrosine residue fluorescence is known to limit the use of tryptophan or tyrosine fluorescence quenching assays to study ligand cobinding to heme-bound proteins (14). An additional study warned against the use of fluorescence-based substrates in assays studying heme-binding proteins (e.g., catalase, hemoglobin) because heme quenching of the fluorescent signal causes assay artifacts (15). Consistent with these studies, we found that heme dose-dependently quenched the fluorescence of fluorophores with excitation and emission wavelengths ranging from 495 nm to 785 nm ( Fig.…”
Section: Heme-dependent Artifacts In Fluorescence-based Assaysmentioning
confidence: 99%
See 4 more Smart Citations
“…Heme quenching of pocket tryptophan and tyrosine residue fluorescence is known to limit the use of tryptophan or tyrosine fluorescence quenching assays to study ligand cobinding to heme-bound proteins (14). An additional study warned against the use of fluorescence-based substrates in assays studying heme-binding proteins (e.g., catalase, hemoglobin) because heme quenching of the fluorescent signal causes assay artifacts (15). Consistent with these studies, we found that heme dose-dependently quenched the fluorescence of fluorophores with excitation and emission wavelengths ranging from 495 nm to 785 nm ( Fig.…”
Section: Heme-dependent Artifacts In Fluorescence-based Assaysmentioning
confidence: 99%
“…To support our ITC results, we performed solution NMR spectroscopy-a structural technique that provides information about the dynamics and structure (via changes to the chemical environment of individual atoms) in a protein at atomic resolution. Titration of NCoR ID peptide into 15 N-labeled REV-ERBβ LBD can 1) validate that the interaction occurs in the presence of heme, 2) qualitatively reflect the strength of the interaction relative to apo (ligand-free)-REV-ERBβ LBD, and 3) highlight the residues most likely involved in binding (16). We previously obtained backbone NMR chemical shift assignments for REV-ERBβ LBD (17).…”
Section: Heme and Ncor Peptides Cobind To The Rev-erbβ Lbdmentioning
confidence: 99%
See 3 more Smart Citations